Inhibition of Sar1b, the Gene Implicated in Chylomicron Retention Disease, Impairs Migration and Morphogenesis of Developing Cortical Neurons. (21st November 2020) - Li, Xue; Yan, Meifang; Guo, Zhiqiang; Yan, Li; Feng, Ruru; Zhu, Hao; Tu, Xiaomeng; Yu, Sidney; Chen, Jie-Guang
Highlights: CMRD patients with SAR1B mutations show hypocholesterolemia and neurologic deficits. Sar1b knockdown in mice blocks radial migration and axon genesis of cortical neurons. Human mutant SAR1B(D137N) exerts a dominant-negative effect on the migration in mice. Loss of SAR1B in the brain may directly cause neurologic deficits of CMRD. Abstract: Chylomicron Retention Disease (CMRD) is a rare inherited lipid malabsorption syndrome that exhibits a recessive hypocholesterolemia in infants. CMRD has been associated with genetic mutations of SAR1B—a member of the Arf GTPase family involved in the secretory pathway from the endoplasmic reticulum to the Golgi. CMRD patients suffer from multiple neurological deficits, the etiologies of which remain unclear. In this study, we found that Sar1b protein is expressed in developing mouse neocortex. The knockdown of Sar1b does not affect the proliferation and mitotic exit of the neural progenitors but inhibits the radial migration of the newborn cortical neurons. At postnatal day 3, the neurons stalled in the white matter fail to develop axons across the midline of the corpus callosum, resulting in the loss of the neurons later on. hSAR1B(D137N), a CMRD-associated mutant of SAR1B, also impairs the positioning of the cortical neurons in the mouse brain, suggesting a dominant-negative effect by the human heterozygous mutant. The results indicate that SAR1B is crucial to radial migration and axon morphogenesis of the cortical neurons. Our study reveals a cell-autonomous action of Sar1b, which is unrelated to lipid absorption from the gut, on the development of the cerebral cortex.